Hard Truths Of Being A Doctor Volume 2 Life and Challenges - Dr. Pagalavan Letchumanan
These books will provide readers a deep insight to the reality of the medical field and healthcare system in Malaysia, and the misconceptions of doctors that society has blindly clung to for generations. Dr Pagalavan combines his experience with selected articles to illustrate the concerns on the mushrooming of medical schools, the quality of medical education, and the surplus of doctors in Malaysia and other countries.